Preparing youth with disabilities for employment: An analysis of vocational rehabilitation case services data. - Poppen, Marcus; Lindstrom, Lauren; Unruh, Deanne; Khurana, Atika; Bullis, Michael (Journal of Vocational Rehabilitation, 2017)
BACKGROUND: Despite national efforts to improve post-school outcomes, many students with disabilities are unprepared to enter the workforce. Coordination with Vocational Rehabilitation (VR) can offer opportunities for improved employment outcomes. OBJECTIVE: This study examined OregonVRdata to identify predictors of positive closure status for youth with disabilities. METHODS: Researchers used logistic regression to explore the effects of individual, in-school, post-school and contextual factors on VR case closure status among 4,443 young adults with disabilities who received and completed services from Oregon VR between 2003 and 2013. RESULTS: Being female, having a mental illness, traumatic brain injury, multiple disabilities, interpersonal or self-care impediments to employment, receiving SSI, and closing with VR in periods of high unemployment reduce the likelihood of a positive VR closure. Participating in a collaborative transition program, earning a high school completion certificate, receiving a greater number of VR services, closing below the median number of days to closure, and closing in low unemployment periods increase the likelihood of a positive VR case closure status. CONCLUSION: These findings highlight specific barriers to employment for vulnerable groups of young adults with disabilities, and identify service and contextual factors that can support positive employment outcomes.